2017
DOI: 10.4049/jimmunol.1601546
|View full text |Cite
|
Sign up to set email alerts
|

IL-13–Mediated Regulation of Learning and Memory

Abstract: The role of proinflammatory cytokines in cognitive function has been investigated with both beneficial and possible detrimental effects, depending on the cytokine. More recently, the type 2 IL-4 has been demonstrated to play a role in cognition. In this study, using the Morris water maze task, we demonstrate that IL-13-deficient mice are significantly impaired in working memory as well as attenuated reference memory, both functions essential for effective complex learning. During the learning process, wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 34 publications
9
84
1
2
Order By: Relevance
“…We also collected evidence that IL-13 is produced in both the pars compacta (SNc) and the pars reticularis (SNr) regions of the substantia nigra, and that cellular sources comprises microglia and neurons, including a fraction of TH-positive ones. Neuronal expression of IL-13 was previously reported in the hippocampus and the cortex following an experimental ischemic insult [31, 32], and recent studies suggested a role of this cytokine in cognitive functions [33]. Our findings showed that stress can regulate IL-13 production locally and suggest the intriguing possibility that it may act in a paracrine or, in the case of TH neuron, possibly even in an autocrine fashion.…”
Section: Discussionsupporting
confidence: 74%
“…We also collected evidence that IL-13 is produced in both the pars compacta (SNc) and the pars reticularis (SNr) regions of the substantia nigra, and that cellular sources comprises microglia and neurons, including a fraction of TH-positive ones. Neuronal expression of IL-13 was previously reported in the hippocampus and the cortex following an experimental ischemic insult [31, 32], and recent studies suggested a role of this cytokine in cognitive functions [33]. Our findings showed that stress can regulate IL-13 production locally and suggest the intriguing possibility that it may act in a paracrine or, in the case of TH neuron, possibly even in an autocrine fashion.…”
Section: Discussionsupporting
confidence: 74%
“…They included known ILC2 products such as Areg , Arg1 , and Bmp7 , as well as previously unreported effector molecules such as Vegfc and Lif (Fig. 5, I and J; Brombacher et al, 2017; Chen and Trapp, 2016; Da Mesquita et al, 2018; Davis and Pennypacker, 2018; de Rivero Vaccari et al, 2009; Ito et al, 2019; Kiyota et al, 2018; Monticelli et al, 2016; Nussbaum et al, 2013; Robinette et al, 2015). A number of pro-inflammatory cytokines, such as Il1a , Il1b , Il18 , Il15, and Tnf , were highly expressed by microglia in the aged brain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of immune-mediated cognitive protection are not yet fully understood. Th2 T cell–derived cytokines IL-4 and IL-13 have been shown to preserve spatial learning and memory through reducing inflammation and promoting neurogenesis (Brombacher et al, 2017; Derecki et al, 2010). Regulatory T cells (T reg cells) may also alleviate cognitive decline in mouse models of Alzheimer’s disease, possibly by constraining neuroinflammation (Baruch et al, 2015; Dansokho et al, 2016; Ito et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the immune compartment in the meninges was implicated in neuronal function (75). Notably, IL-4 and IL-13 production by meningeal T cells appears to contribute to the maintenance of cognitive function in mice (74,95). Furthermore, production of IFN-γ in the SAS directly regulates social behavior in mice (96).…”
Section: Communication Between the Cns Compartmentsmentioning
confidence: 99%